1997
DOI: 10.1902/jop.1997.68.7.618
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Serum Antibody Levels and Subgingival Colonization of Porphyromonas gingivalis in Patients With Various Types of Periodontitis

Abstract: Porphyromonas Gingivalis is considered to be an important pathogen in periodontitis. The present study investigates the relationship between serum anti‐P. gingivalis IgG antibody levels and the subgingival distribution of P. gingivalis in patients with periodontitis. We examined subgingival plaque samples from 15 patients with adult periodontitis (AP), 8 patients with early‐onset periodontitis (EOP), and 6 clinically healthy individuals. The samples were collected from periodontal pockets or gingival crevices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 45 publications
4
58
1
Order By: Relevance
“…The distribution of periodontopathic organisms in gingival plaque is closely related to antibody levels to the intact bacteria in serum. For example, studies have shown a direct relationship between the serum anti-P gingivalis IgG levels and subgingival colonization by P gingivalis 48 consistent with a systemic antibody response as a reflection of the host response to infections by periodontal organisms. Increases in systemic antibody response to organisms have also been associated with episodes of periodontal disease activity.…”
Section: Discussionmentioning
confidence: 89%
“…The distribution of periodontopathic organisms in gingival plaque is closely related to antibody levels to the intact bacteria in serum. For example, studies have shown a direct relationship between the serum anti-P gingivalis IgG levels and subgingival colonization by P gingivalis 48 consistent with a systemic antibody response as a reflection of the host response to infections by periodontal organisms. Increases in systemic antibody response to organisms have also been associated with episodes of periodontal disease activity.…”
Section: Discussionmentioning
confidence: 89%
“…Although the pathogens can be readily sampled from the mouth and identified and quantified by any of a variety of laboratory techniques, oral sampling was not conducted in NHANES III. Several studies have shown significant, positive correlations between specific IgG antibody levels and levels of these pathogens in the mouth [33][34][35] ; however, those studies were relatively small, and correlations were not consistently strong. Because antibody responses to these and other pathogens are influenced by a variety of host factors, serum antibody levels may not be an accurate measure of pathogen exposure.…”
Section: Discussionmentioning
confidence: 99%
“…SusC protein is an essential receptor for uptake and utilization of certain starches and intermediate-sized maltooligosaccharides, apparently powered by a Bacteroides homologue of the TonB complex (28,29). With respect to RagA, the ragAB locus has been validated as a virulence factor of P. gingivalis tissue damage and in vivo survival, and RagA and RagB are recognized targets of disease-associated periodontal antibody responses (11,21,22). On this basis, RagA is implicated in P. gingivalis-associated periodontal disease.…”
Section: Discussionmentioning
confidence: 99%